THE IMPACT OF DIET ON MENTAL HEALTH: A COMPREHENSIVE REVIEW (International Journal of Food and Nutritional Sciences, 2020)
This paper explores the relationship between diet and mental health, focusing on the role of nutrition in the prevention and treatment of mental health disorders. The review examines current research linking dietary patterns, specific nutrients, and mental health outcomes such as depression, anxiety, and cognitive disorders. It also discusses mechanisms such as the gut-brain axis, neuroinflammation, and oxidative stress, which may explain the impact of nutrition on mental well-being. Findings suggest that a diet rich in whole foods, has protective effects on mental health, while Western dietary patterns are associated with higher risks of mental health issues.